2018
DOI: 10.1111/ejn.13894
|View full text |Cite
|
Sign up to set email alerts
|

Heroin seeking becomes dependent on dorsal striatal dopaminergic mechanisms and can be decreased by N‐acetylcysteine

Abstract: The alarming increase in heroin overdoses in the USA is a reminder of the need for efficacious and novel treatments for opiate addiction. This may reflect the relatively poor understanding of the neural basis of heroin, as compared to cocaine, seeking behaviour. While cocaine reinforcement depends on the mesolimbic system, well-established cocaine seeking is dependent on dorsolateral striatum (aDLS) dopamine-dependent mechanisms which are disrupted by N-acetylcysteine, through normalisation of corticostriatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 50 publications
2
59
0
Order By: Relevance
“…The dorsolateral striatum (DLS) and its dopaminergic inputs from the substantia nigra pars compacta (SNc) are a proposed point of convergence between the mechanisms of habit and compulsion. Dopamine signaling in the DLS is required for habit (Faure et al, 2005), and blocking dopamine signaling in the DLS can inhibit drug seeking for cocaine or alcohol (Corbit et al, 2012;Hodebourg et al, 2018;Murray et al, 2012;Pacchioni et al, 2011;Vanderschuren et al, 2005). The inhibition of drug seeking by DLS dopamine signaling blockade precedes the development of compulsive drugseeking, but can predict which animals will develop it (Giuliano et al, 2019;Willuhn et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The dorsolateral striatum (DLS) and its dopaminergic inputs from the substantia nigra pars compacta (SNc) are a proposed point of convergence between the mechanisms of habit and compulsion. Dopamine signaling in the DLS is required for habit (Faure et al, 2005), and blocking dopamine signaling in the DLS can inhibit drug seeking for cocaine or alcohol (Corbit et al, 2012;Hodebourg et al, 2018;Murray et al, 2012;Pacchioni et al, 2011;Vanderschuren et al, 2005). The inhibition of drug seeking by DLS dopamine signaling blockade precedes the development of compulsive drugseeking, but can predict which animals will develop it (Giuliano et al, 2019;Willuhn et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The role of DA is also explored in studies of heroin addiction where, similarly to cocaine addiction (Everitt, ), control over heroin‐seeking behaviour appears to shift to dorsolateral striatum DA‐dependent mechanisms after extended training. Rats acquired heroin self‐administration and were subsequently trained to seek heroin daily over prolonged periods of time under the control of drug‐paired cues (Hodebourg et al ., ). Again, quantitatively similar to the patterns observed with cocaine, such dorsolateral striatum‐dependent cue‐controlled heroin seeking was disrupted by N‐acetylcysteine, which restores cortico‐striatal glutamate homeostasis (Hodebourg et al ., ).…”
Section: Preclinical Modelsmentioning
confidence: 97%
“…Rats acquired heroin self‐administration and were subsequently trained to seek heroin daily over prolonged periods of time under the control of drug‐paired cues (Hodebourg et al ., ). Again, quantitatively similar to the patterns observed with cocaine, such dorsolateral striatum‐dependent cue‐controlled heroin seeking was disrupted by N‐acetylcysteine, which restores cortico‐striatal glutamate homeostasis (Hodebourg et al ., ).…”
Section: Preclinical Modelsmentioning
confidence: 97%
“…Recent evidence showed that NAC markedly decreases cue‐controlled cocaine and heroin seeking behaviour in rats trained under a second order schedule of reinforcement. These effects were observed both at early and late stages of training, when the behaviour is controlled by aDLS‐independent and aDLS‐dependent mechanisms respectively (Hodebourg et al., ; Murray, Everitt, & Belin, ) (Figure ).…”
Section: Targeting Astrocytes To Restore Glutamate Homeostasis: a Valmentioning
confidence: 97%
“…(a) Overtraining under a second order schedule of reinforcement for cocaine or heroin promotes the devolvement of control over behaviour to aDLS dopamine‐dependent mechanisms in that only late, and not early, stage drug‐seeking behaviour is dose‐dependently decreased by bilateral intra‐ aDLS infusions of the dopamine receptor antagonist α‐flupenthixol. (b) N‐acetylcysteine is equally effective at reducing cocaine and heroin seeking behaviour at early, aDLS ‐independent, and late, aDLS dopamine‐dependent, performance stage (Hodebourg et al., , originally published under a Creative Commons Attribution License ( CC BY )). AL , active lever; Veh, vehicle; aDLS , anterior dorsolateral striatum.…”
Section: Targeting Astrocytes To Restore Glutamate Homeostasis: a Valmentioning
confidence: 99%